Efficiency Evaluation of Neuroprotection for Therapeutic Hypothermia to Neonatal Hypoxic-Ischemic Encephalopathy - Weng, Bowen; Yan, Chongbing; Chen, Yihuan; Gong, Xiaohui; Cai, Cheng (Frontiers in Neuroscience, 2021)
Abstract Background: To evaluate the safety and neurological outcomes of therapeutic hypothermia to neonatal hypoxic-ischemic encephalopathy (HIE). Methods: Medical records of 61 neonates with moderate to severe HIE were retrospectively enrolled and subjected to therapeutic hypothermia group (n =36) and conventional therapy group (n = 25). Results: No significant difference in the incidence of severe adverse events was found between two groups. Minimum and maximum voltages of amplitude-integrated electroencephalography (aEEG) recording results showed statistically significant differences in therapeutic hypothermia group after 72 hours. The neonatal behavioral neurological assessment (NBNA) on the 28th day after birth and Bayley Scales of Infant Development, second edition (BSID Ⅱ) scores at 18 months old were significant higher on therapeutic hypothermia group than conventional therapy group. Conclusions: Therapeutic hypothermia for neonates with moderate to severe HIE improved the development of nervous system in 0-18 months old infants and showed predominant role in reducing death and major neuron development associated disabilities.